Migration of dendritic cells: physical principles, molecular mechanisms, and functional implications. Issue 1 (10th October 2013) - Heuzé, Mélina L.; Vargas, Pablo; Chabaud, Mélanie; Le Berre, Maël; Liu, Yan‐Jun; Collin, Olivier; Solanes, Paola; Voituriez, Raphaël; Piel, Matthieu; Lennon‐Duménil, Ana‐Maria
Summary: Dendritic cells (DCs) constitute a complex cell population that resides in both peripheral tissues and lymphoid organs. Their major function in tissues is to patrol their environment in search of danger‐associated antigens to transport to lymph nodes and present to T lymphocytes. This process constitutes the first step of the adaptive immune response and relies on specific DC properties, including a high endocytic capacity as well as efficient motility in confined three‐dimensional environments. Although cell motility has been widely studied, little is known on how the geometric characteristics of the environment influence DC migration and function. In this review, we give an overview of the basic physical principles and molecular mechanisms that control DC migration under confinement and discuss how such mechanisms impact the environment‐patrolling capacity of DCs.